A Case of Osler-Weber-Rendu Syndrome Complicated with Nasal Septum Perforation - Tsogbadrakh, Odgerel; Ogoosambuu, Injinaash; Jukhai, Layala; Davaasumberel, Munkhhbaatar; Alexandr, Khatanbaatar (Central Asian Journal of Medical Sciences, 2020)
Objectives: Hereditary hemorrhagic telangiectasia (Osler-Weber-Rendu disease) is a rare autosomal dominant disorder characterized by multiple mucocutaneous telangiectasias and visceral arteriovenous malformations. We report the first case of Randu-Osler-Weber disease complicated with nasal septum perforation. Method: Diagnosis was based on physical examination and genetic testing. Results: A 52 years old female presented to the Mongol-Japan Teaching Hospital for evaluation of anemia and recurrent epistaxis. On physical examination, telangiectasias were found on eye mucous, tongue tip, palms, and fingers. An ACVRL 1 mutation was detected by genetic testing. Conclusion: On the basis of clinical features in this patient telangiectatic lesions in nasal cavity lead to epistaxis which is more common than mucocutaneous telangiectasia in HTT. Recurrent nose bleeding leads to iron deficiency anemia.